The expression level and prognostic value of HIPK3 among non-small-cell lung cancer patients in China - Liu Y (OncoTargets and Therapy, 2018)
Yifei Liu,1,* Li Qian,1,* Juanjuan Yang,1 Hua Huang,1 Jia Feng,1 Xiaoli Li,1 Tingting Bian,1 Honggang Ke,2 Jian Liu,3 Jianguo Zhang1 1Department of Pathology, Affiliated Hospital of Nantong University, Nantong, Jiangsu, China; 2Department of Thoracic Surgery, Affiliated Hospital of Nantong University, Nantong, Jiangsu, China; 3Department of Chemotherapy, Affiliated Hospital of Nantong University, Nantong, Jiangsu, China *These authors contributed equally to this work Background: Lung cancer is one of the most common malignancies in the world and is at the forefront of causes of all cancer deaths. Identification of new prognostic predictors or therapeutic targets might improve a patient’s survival rate. Purpose: The Homeodomain interacting protein kinases (HIPKs) function as modulators of cellular stress responses and regulate cell differentiation, proliferation and apoptosis, but the function of HIPK3 is remain unknown. Patients and methods: We used quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting methods to detective the expression of HIPK3. A total of 206 samples were obtained from patients and Immunochemical evaluation to determine HIPK3 protein expression. HIPK3 protein levels in in non-small cell lung cancer (NSCLC) were correlated with the clinical characteristics of patients and their 5-year survival rate. In addition, HIPK3 knockdown by specific RNAi promoted cell proliferation, migration, and invasion in A549 and HCC827 cancer cell lines. Results: The quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting methods to demonstrate that HIPK3 expression was significantly down-regulated in non-small cell lung cancer (NSCLC) tissues compared with that in normal lung tissues. At the same time, the results of immunohistochemistry assays showed that low expression of HIPK3 was significantly associated with pathology grade; tumor, node, and metastases (TNM) stage; lymph node metastasis; Ki-67 expression; and the 5-year survival rate in NSCLC patients. Univariate analysis revealed that HIPK3 expression, Ki-67 expression, tumor diameter, TNM stage, and age were significantly associated with a poor prognosis. The multivariable analysis illustrated that HIPK3, tumor diameter, TNM, Ki-67 expression, and age had effects on the overall survival of NSCLC patients independently. Kaplan-Meier survival curves revealed that NSCLC patients with a lower HIPK3 expression had a poorer prognosis. In addition, in vivo results also confirmed that HIPK3 over-expression could inhibit tumor growth. Conclusion: Our findings confirmed that low expression of HIPK3 in NSCLC tissues was significantly correlated with poor survival rates after curative resection. HIPK3 could potentially be used as a valuable biomarker in the prognosis of the survival of NSCLC patients. Keywords: HIPK3, non-small-cell lung cancer, immunohistochemistry, tumor suppressor gene, prognosis, biomarker